The Ruby Interpreter - Hutton, Graham (Department of Computing Science, 1993)
Ruby is a relational calculus for designing digital circuits. This document is a guide to the Ruby interpreter, which allows a special class of $quot;implementable$quot; Ruby programs to be executed. The Ruby interpreter is written in the functional programming language Lazy ML, and is used under the interactive Lazy ML system.